1997
DOI: 10.1074/jbc.272.7.4269
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional Structure of Myelin Basic Protein

Abstract: A computational model of myelin basic protein (MBP) has been constructed based on the premise of a phylogenetically conserved ␤-sheet backbone and on electron microscopical three-dimensional reconstructions. Many residues subject to post-translational modification (phosphorylation, methylation, or conversion of arginines to citrullines) were located in loop regions and thus accessible to modifying enzymes. The triproline segment (residues 99 -101) is fully exposed on the back surface of the protein in a long c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
26
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 92 publications
(31 citation statements)
references
References 43 publications
5
26
0
Order By: Relevance
“…4C) coincided with a peak in disorder probability. A similar finding was made from comparison with the model of the MBP three-dimensional structure by Ridsdale et al (10). In this model, the MBP structure carries a central ␤ sheet with five strands.…”
Section: The Ga Peptides Are Similar To the Least-structured Regions supporting
confidence: 66%
See 2 more Smart Citations
“…4C) coincided with a peak in disorder probability. A similar finding was made from comparison with the model of the MBP three-dimensional structure by Ridsdale et al (10). In this model, the MBP structure carries a central ␤ sheet with five strands.…”
Section: The Ga Peptides Are Similar To the Least-structured Regions supporting
confidence: 66%
“…A model of the MBP three-dimensional structure showed that MBP assumes a conformation similar to an open C with a central ␤-sheeted region surrounded by large loop regions rich in charged amino acid residues, which make contact with the cell membrane (10). The model was supported by small angle xray scattering (SAXS) studies of MBP in the presence of lipids and detergents (11).…”
mentioning
confidence: 64%
See 1 more Smart Citation
“…Following the pilot demonstration indicating that the stilbene Congo red derivative 1,4‐bis(p‐aminostyryl)‐2‐methoxy benzene, could be used as a myelin tracer suitable for PET imaging,6 a similar affinity for myelin was reported for other stilbene derivatives 7, 8, 9, 10. These tracers, all previously known as amyloid markers, were hypothesized to bind to proteins characterized by a similar conformation contained in amyloid plaques and myelin 11, 12. On this basis, Pittsburgh compound B (PiB), a thioflavin compound binding to amyloid plaques, was also identified as a promising myelin tracer suitable for human PET studies 13.…”
mentioning
confidence: 93%
“…Presently the tertiary structure of MBP is unknown, with the most detailed predictions coming from Martenson (12) and Stoner (13) in the mid-1980s. In these models, as well as in a newer model based upon further research on an electron microscopy single-particle reconstruction, residues 86 -92 are found in a ␤-sheet (14,15). Using [ 1 H]NMR and circular dichroic spectropolarimetry of various MBP peptides with detergent micelles, Mendz et al (16) suggested that there were discrete interaction sites in the protein, one of which could be a helix between residues 87 and 97.…”
mentioning
confidence: 99%